Role of Free Tissue Transfer in Facial Trauma - Kim, Roderick Y.; Sokoya, Momofiyin; Williams, Fayette C.; Shokri, Tom; Ducic, Yadranko (Facial Plastic Surgery, 2019)
For large composite traumatic defects of the head and neck, free tissue transfer presents a reconstructive allowing for the reconstitution of both form and function. Furthermore, the ability to provide bulk, soft, and hard tissue, as well as immediate dental rehabilitation, makes free tissue transfer an efficient and attractive option for head and neck reconstruction. Herein, we discuss the utility of free tissue transfer in facial trauma, its problems, complications, and controversies.
Keywords: maxillofacial trauma; free tissue transfer; free flap; head and neck reconstruction